Determinants of sleep disturbances in Rett syndrome: Novel findings in relation to genotype. Issue 9 (3rd June 2016) - Boban, Sharolin; Wong, Kingsley; Epstein, Amy; Anderson, Barbara; Murphy, Nada; Downs, Jenny; Leonard, Helen
Abstract : Rett syndrome is a rare but severe neurological disorder associated with a mutation in the methyl CpG binding protein 2 ( MECP2 ) gene. Sleep problems and epilepsy are two of many comorbidities associated with this disorder. This study investigated the prevalence and determinants of sleep problems in Rett syndrome using an international sample. Families with a child with a confirmed Rett syndrome diagnosis and a MECP2 mutation registered in the International Rett Syndrome Phenotype Database (InterRett) were invited to participate. Questionnaires were returned by 364/461 (78.9%) either in web‐based or paper format. Families completed the Sleep Disturbance Scale for Children and provided information on the presence, nature, and frequency of their child's sleep problems. Multivariate multinomial regression was used to investigate the relationships between selected sleep problems, age group, and genotype and linear regression for the relationships between sleep disturbance scales and a range of covariates. Night waking was the most prevalent sleep problem affecting over 80% with nearly half (48.3%) currently waking often at night. Initiating and maintaining sleep was most disturbed for younger children and those with a p.Arg294* mutation. Severe seizure activity was associated with poor sleep after adjusting for age group, mutation type, and mobility. We were surprised to find associations between the p.Arg294* mutation and some sleep disturbances given that other aspects of its phenotype are milder. These findings highlight the complexities of aberrant MECP2 function in Rett syndrome and explain some of the variation in manifestation of sleep disturbances. © 2016 Wiley Periodicals, Inc.